“Tiempo de exposición a computadoras como factor asociado a Síndrome Visual Informático en estudiantes de Estomatología de la UNT, 2021” - Gamarra Herrera, Daniel Antonio (2022)
he development of this research was framed in a context, where the excessive use of computers and other computer equipment, have affected people's quality of life. Given this, the following objective has been proposed: To determine the association between the time of exposure to computers and the Visual Computer Syndrome in Stomatology students of the UNT, 2021. The type of research was basic, descriptive and cross-sectional, having considered a sample of 89 students, where the data collection instrument was the questionnaire. The results have indicated that there has been an association between the time of exposure to computers and the Computer Visual Syndrome, as a result of a significance value lower than 0.050, where there has been a correlation value of 0.234, having been a relationship of the "directly proportional" type. Whereas, it has been concluded that it has not been possible to demonstrate an incidence between the presence of computer visual syndrome and the age of the students, their gender; as well as the number of years of study that they have maintained in the educational establishment.